PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI PADA UMKM ONE BOWL SOUP - Ng, Irvin; Junita; Viviani; Oktarianto, Eddy; Lindawati; Jovianto; Joey (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
A MSME called One Bowl Soup offers Singaporean fried fish soup. In April 2019, One Bowl Soup opened in the A2 Foodcourt. It will be crucial for the business to manage production capacity when operating. It was discovered by operating a business in the foodcourt region that the foodcourt will have a large number of visitors during vacations, specifically weekends, school breaks, and national holidays. The fact that One Bowl Soup MSMEs are active and integrated in the majority of significant commercial apps, such as Go-Food, GrabFood, and Shopee Food, is another aspect that affects demand for these MSMEs. One Bowl Soup is open from 9.00 WIB until 21.00 WIB. According to the average quarterly sales of One Bowl Soup MSMEs during the past three years, there was a spike in demand during the first, second, and fourth quarters due to national holidays, which are widely observed by Indonesians. Little was done by One Bowl Soup UMKM to foresee these changes in demand. Therefore, One Bowl Soup must increase its preparation efforts to anticipate demand swings around national holidays.